P207 Ambient air pollution and admissions to hospital with exacerbations of asthma. (15th November 2017) - Thompson, F; Hujan, A; Richardson, M; Woltmann, G; Siddiqui, S; Gonem, S
Abstract : Background: Air pollution has been linked to increased morbidity and mortality associated with a number of chronic health conditions including asthma. We hypothesised that levels of ambient air pollution would be related to the number of hospital admissions with exacerbations of asthma. Methods: Data on asthma admissions to a large acute NHS trust in the East Midlands were extracted using discharge diagnosis codes over a five-year period from April 2011 to March 2016. Ambient air pollution levels during this period were obtained from the website of the Department for Environment, Food and Rural Affairs. These data were based on a single monitoring station located in the centre of the City which recorded hourly readings of ozone, nitrogen oxides and small particulate matter (PM2.5 ). Daily mean data were utilised in the analysis. The effect of ambient air pollution on daily admissions for asthma was assessed using a generalised linear model in R version 3.3.1. Independent variables in the model were time, Ozone, NO, NOx and PM2.5 . Fourier terms to capture any long-term trend or seasonality where also included in the model. Delayed exposure effects where investigated by fitting separate constrained lag models. Results: During the period from April 2011 to March 2016 there were 4204 admissions due to asthma exacerbations (71% female, mean age 48 years). Admission numbers increased progressively from 726 in 2011/12 to 1043 in 2015/16. Admissions were most frequent in the month of December (2.9 per day) and least frequent in August (1.5 per day). None of Ozone, NO, NOx and PM2.5 or their lagged terms were found to be independent predictors of daily admissions for asthma. Conclusion: Ambient air pollution measured at a single fixed monitoring station within a city is not able to predict the frequency of admissions due to asthma. Further research on the health effects of air pollution should make use of more detailed assessments of city-wide exposure, for instance by utilising satellite imaging and geospatial mapping.